Arctic will [large type] - Sundell, Joanne (Sundell, Joanne. Watch eyes trilogy, 2017)
As the 1910 Alaska sled dog race approaches, Anya and Rune must prevail over dark spirits bent on killing every Chukchi dog on Native Earth.